Characteristics of pulsed electric field cardiac ablation porcine treatment zones with a focal catheter. (16th November 2022) - Verma, Atul; Neal, Robert; Evans, John; Castellvi, Quim; Vachani, Armaan; Deneke, Thomas; Nakagawa, Hiroshi
Abstract: Objectives: Pulsed electric field (PEF) therapies employ punctuated energy delivery to kill cells in a volume of tissue through mechanisms that are not dependent on thermal processes. A key component to successful cardiac ablation procedures is ensuring the generation of transmural, contiguous ablation zones, which requires in‐depth knowledge regarding treatment sizes for a given therapeutic application. Methods: In this study, a series of acute treatments were delivered to porcine ventricles, where triphenyl tetrazolium chloride (TTC) vitality stain was used to identify treatment effect sizes for the three focal monopolar CENTAURI PEF cardiac ablation energy settings. Results: Treatment depths were 5.7, 7.2, and 8.2 mm for the 19, 22, and 25 A energy settings, respectively. Gross pathology indicated umbral zones of hemorrhage surrounded by pale avital TTC‐negative‐negative tissue, which contrasted significantly from radiofrequency ablation (RF) controls. Histologically, treatment zones are identified by regions of contraction band necrosis and cardiomyocytolysis, which contrasted with RF control lesions composed primarily of coagulation necrosis. Conclusions: Together, these data indicate the ability for focal monopolar PEF treatments to generate deep treatment zones in cardiac ablation without incurring the gross or histological coagulative characteristics of RF thermal lesions.